KONSTRUKSI ARCHIPELAGIC STATE PRINCIPLE DALAM PEMBANGUNAN HUKUM LAUT INTERNASIONAL - Ria Tri Vinata (Lembaga Kajian Hukum, Fakultas Hukum, Universitas Singaperbangsa Karawang, 2019)
The archipelago consists of several coastal islands and two archipelagic countries in Southeast Asian in fighting for the concept of the Archipelagic State Principle, namely Indonesia and the Philippines. In applying the Archipelagic State Principle, it is necessary to consider the specific circumstances of the country which are not only focused on geographical factors, but also on natural characteristics and in particular historical backgrounds. The method of writing in this study is the normative research and the statute approach as well as the historical approach by examining the ontological basis of the travaux preparatory archipelagic principle. The results of the study are that the Archipelagic state Principle was championed by the archipelagic state which is essentially the application of the principle of a straight line in an island nation, although this principle is based on international law only applies to island nations and coastal states.